Presbyopic lens exchange (PRELEX) cataract surgery outcomes with implantation of a rotationally asymmetric refractive multifocal intraocular lens: femtosecond laser-assisted versus manual phacoemulsification - Žiak, Peter; Halička, Juraj; Mojžiš, Peter; Kapitánová, Karolína; Michal, Javorka; Piñero, David P (International ophthalmology, 2019)
PURPOSE: To compare the visual and refractive outcomes obtained with the implantation of a rotationally asymmetric refractive multifocal IOL after femtosecond laser-assisted cataract surgery (FLACS) and conventional lens extraction (CLE). METHODS: A total of 78 eyes of 58 patients that had undergone conventional phacoemulsification (36 eyes, CLE group) or FLACS (37 eyes, FLACS group) with the implantation of the toric multifocal IOL LU-313 MF30T (Oculentis, Germany) were enrolled in this retrospective study. Mean age was 57.0 years at the time of surgery, ranging from 44 to 69 years. Visual and refractive outcomes were evaluated during a 12-month follow-up. Likewise, contrast sensitivity was assessed at the end of the follow-up. RESULTS: Significant improvements were observed in both groups in uncorrected distance (UDVA) and near visual acuity (UNVA) at 1 month postoperatively (p < 0.001). Differences between groups in these parameters as well as in sphere and cylinder did not reach statistical significance during the whole follow-up (p ≥ 0.079), except for UNVA only at 12 months postoperatively (p = 0.018). Concerning corrected near visual acuity, only significant differences between groups were found preoperatively (p = 0.020). Furthermore, only a minimal but significant difference between groups was found at 12 months postoperatively in contrast sensitivity for the spatial frequency of 18 cycles/° (p = 0.029). CONCLUSIONS: The rotationally asymmetric toric multifocal IOL LU-313 MF 30T provides good visual rehabilitation for near and distance vision after presbyopic lens extraction in eyes with preexisting astigmatism, independently whether the cataract surgery is performed with the FLACS or conventional technique.
Keywords: dospělí; Female; Refractive lens extraction; Clear lens extraction; Adult; Refraction, Ocular; ženské pohlaví; fakoemulzifikace; refrakce oka; lidé; Phacoemulsification; multifokální intraokulární čočky; Multifocal intraocular lens; Presbyopia; retrospektivní studie; Male; Multifocal Intraocular Lenses; Rotationally asymmetric multifocal intraocular lens; Aged; Femtosecond laser-assisted cataract surgery; citlivost na kontrast; Lens Implantation, Intraocular; lidé středního věku; senioři; mužské pohlaví; implantace nitrooční čočky; zraková ostrost; Visual Acuity; Retrospective Studies; Middle Aged; Contrast Sensitivity; Humans